On the role of national ratings in the development of higher educational institutions (universities) - Mete Osman Kemal (Informaciâ i Innovacii, 2018)
One of the most common approaches to comparing the results of the activities of higher education institutions is the use of indicators of bibliometry or sciencemetry. It is these indicators that formed the basis of the approach of the article. The article presents not only the results of the rating, but also various materials, a methodology for compiling national ratings, useful materials that allow the interpretation of ratings correctly.